2014
DOI: 10.1007/978-94-6265-011-4_8
|View full text |Cite
|
Sign up to set email alerts
|

The WTO and the Doha Negotiation in Crisis?

Abstract: Is the World Trade Organization (WTO) in a legitimacy crisis and might the protracted Doha negotiations be evidence of it? This article understands the notion of 'legitimacy crisis' as a severe threat to an institution's viability due to fundamental shifts in the legitimising ideas underlying the institution, an external threat to its values or its ability to fulfil its functions. It contends that the WTO is not yet definitely in a legitimacy crisis because the Doha negotiations still reveal the commitment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Although the financial crisis that broke out in 2008 did not challenge the idea that trade should be as free as possible (Subramanian and Kessler, 2013;De Ville and Orbie, 2011), the difficulty in reaching agreements at the multilateral level put into question the ability of the WTO to be effective (Narlikar, 2012;Bhagwati, 2008). It may even be argued that the difficulties to enact the mini-package agreement achieved in December 2013 in the Bali Ministerial Meeting have not done much good to restore the WTO image (Herwig, 2013). Can we therefore consider that since 2009 and at least up until 2013 the DR negotiations difficulties were too severe?…”
Section: Defining and Measuring The New Independent Variablementioning
confidence: 99%
See 1 more Smart Citation
“…Although the financial crisis that broke out in 2008 did not challenge the idea that trade should be as free as possible (Subramanian and Kessler, 2013;De Ville and Orbie, 2011), the difficulty in reaching agreements at the multilateral level put into question the ability of the WTO to be effective (Narlikar, 2012;Bhagwati, 2008). It may even be argued that the difficulties to enact the mini-package agreement achieved in December 2013 in the Bali Ministerial Meeting have not done much good to restore the WTO image (Herwig, 2013). Can we therefore consider that since 2009 and at least up until 2013 the DR negotiations difficulties were too severe?…”
Section: Defining and Measuring The New Independent Variablementioning
confidence: 99%
“…The answer to this key question is not as straightforward as one may think because stalemates in multilateral negotiations are not so rare (Herwig, 2013). As most GATT rounds have tended to be declared in danger at different points in time and have finally led to agreement (Mansfield and Reinhardt, 2003;Cohn, 2002), it is difficult to judge the severity of negotiation difficulties on the bases of the number of years without progress.…”
Section: Defining and Measuring The New Independent Variablementioning
confidence: 99%
“…The literature does not provide a definition of what constitute "difficulties which are too severe", or "stalled" multilateral negotiations, and the answer to this key question is not straight forward because stalemate is not uncommon in multilateral negotiations (Herwig, 2013). Since most GATT rounds tended to be declared "in danger" at different points in time even though they finally led to agreement (Mansfield and Reinhardt, 2003;Cohn, 2002), it is difficult to judge the severity of the challenges facing negotiations on the bases of the number of years without progress.…”
Section: Operationalizing the New Necessary Conditionmentioning
confidence: 99%
“…Although the financial crisis that broke out in 2008 did not directly challenge the idea that trade should be as free as possible (Subramanian and Kessler, 2013;De Ville and Orbie, 2011), the subsequent difficulty of reaching any plurilateral or multilateral agreements put into question the ability of the WTO to be effective (Azevedo, 2015;Narlikar, 2012;Bhagwati, 2008). The difficulties achieving the mini-package agreement in December 2013 at the Bali Ministerial Conference did little to rebuild the WTO's image (Herwig, 2013), and even if the Nairobi Ministerial Conference agreement (on agriculture, export subsidies, and issues affecting least developed countries) in December 2015 was a brief period of optimism, the sectoral agreements reached at the WTO Ministerial Conferences confirmed that the principle of a single undertaking (one large multilateral agreement) of the DDR is dead.…”
Section: Operationalizing the New Necessary Conditionmentioning
confidence: 99%